Visual and Anatomic Outcomes following Cataract Surgery in Patients with Pre-operative Macular Edema Due to Retinal Vein Occlusions Managed with Intravitreal anti-VEGF. (18th May 2020) - Starr, Matthew R.; Mahr, Michael A.; Iezzi, Raymond; Barkmeier, Andrew J.; Bakri, Sophie J.
ABSTRACT: Purpose: The purpose of this study was to investigate the visual and anatomic outcomes in patients with macular edema due to retinal vein occlusions (RVO) who were actively managed with intravitreal anti-vascular endothelial growth factor (VEGF) before and after cataract surgery. Methods: Retrospective, cohort study of all patients with RVO who underwent cataract surgery and were receiving intravitreal anti-VEGF injections from January 1st, 2012 through October 31st, 2018. There were 31 eyes that underwent cataract surgery and received at least one intravitreal anti-VEGF injection for a diagnosis of RVO within 6 months prior to surgery. Data collected included the development of subretinal or intraretinal macular fluid in the 6 months following surgery, timing of injections, number of injections, best corrected visual acuity (BCVA), and central subfield thickness (CST). Results: There was a significant improvement between pre- and post-operative BCVA when comparing all eyes ( p values < .0001) and no significant difference in CST before and after surgery ( p > .05). Eyes without fluid pre-operatively saw an improvement in visual acuity, but with an initial significant increase in CST ( p = .03) that normalized over time ( p = .33) without an increase in frequency of anti-VEGF injections. Conclusion: Patients with cataracts who are actively managed for macular edema due to RVO with anti-VEGF agents may undergo cataract surgery, knowing they will have a transient increase in macular thickness that resolves without adjusting the frequency of intravitreal injections and is not visually significant.